Analisis Tingkat Pencahayaan Alami dan Buatan Ruang-Ruang Kuliah di Science Learning Center (SLC) Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman - Wahyuni, Risma Nur; Natalisanto, Adrianus Inu; Putri, Erlinda Ratnasari; Mislan, Mislan; Supriyanto, Supriyanto (Progressive Physics Journal, 2023)
Light intensity is the intensity of light emitted as a light source in a certain direction. In a building, human safety depends on the level of lighting, and helps create a creative visual environment. Broadly speaking, light sources are divided into two, namely natural light and artificial light. According to the Indonesian National Standard (SNI), the recommended minimum lighting strength for lecture halls is 250 lux. Therefore, this study aims to determine whether the lighting intensity of the lecture hall in the SLC building meets the SNI standard, and to determine the relationship between natural and artificial fluxes in the SLC lecture hall of the Faculty of Mathematics and Natural Sciences, Mulawarman University. This study uses the method of measuring the intensity of illumination with a luxmeter measuring instrument at predetermined measurement points. The results obtained in this study, namely, the intensity of natural and artificial lighting in the lecture hall of the SLC building did not entirely meet the SNI standard, because in use without lights and 6 lights the point is far from the light source. The relationship between natural and artificial lighting flux corresponds to changes in the intensity of natural and artificial lighting with time, the greater the change in lighting intensity with time, the greater the lighting flux in the lecture room with time.